The Influence of the Short Story al-Jababirah by Najib Kailani on Habiburrahman el-Shirazy's Creativity in the Short Story Di Atas Sajadah Cinta - Muh. Ilham Shohib; Ahmad Sirfi Fatoni; Khair, Rahimal (LPPM Institut Studi Islam Sunan Doe, 2024)
This research aims to demonstrate the influence of the short story Al-Jababiroh by Najib Kaelani on Habiburrahman el Shirazy in the production of his short story entitled Di Atas Sajadah Cinta. With regard to the numerous similarities between the two short stories, it can be argued that they represent a form of inspiration and influence from Najib Kaelani to Habiburraman el Shirazy, particularly in the context of his work entitled Al-Jababiroh. This research employs a comparative literary method, namely the comparison of the works of both authors. In addition, the researcher employs the intertextual theory proposed by Julia Kristeva. In this comparison, the researcher finds that Habiburrahman el Shirazy was creative in developing his work. With regard to this form of creativity, the protagonist of Habiburrahman el Shirazy's short story does not undergo the same experience as the male protagonist of Al-Jababiroh. This divergence can even alter the trajectory of the narrative, ultimately culminating in the male protagonist of Habiburrahman el Shirazy's work proposing to the female protagonist, Afirah. Consequently, it can be posited that the short story entitled Di Atas Sajadah Cinta by Habiburrahman el Shirazy underwent expansion, modification, existence, and defamiliarization as initiated by Julia Kristeva.